PENGARUH ETIKA KERJA ISLAM, PERSEPSI DUKUNGAN ORGANISASI, DAN KEPUASAN KERJA TERHADAP PERILAKU KEWARGAAN ORGANISASI PERSPEKTIF ISLAM (Studi pada Dosen UIN Walisongo Semarang) - Putri Susanto, Ayu Diah; Mas’ud, Fuad (Diponegoro Journal of Management, 2023)
ABSTRACT World Class University (WCU) has become a reference for the quality of a university so that it influences the university's strategy to achieve and maintain its ranking. Furthermore, universities need to inspire their lecturers to perform their best and encourage lecturers to assume their responsibilities as citizens. The existence of a lecturer was a significant factor in the progress of a university organization by the contribution of the main task of lecturer which named Tridharma Perguruan Tinggi. This research was intended to assess the influence of Islamic work ethic, perceived organizational support, and job satisfaction on organizational citizenship behavior Islamic perspective. This study was conducted using a quantitative approach on Associate Professor and Full Professor of UIN Walisongo Semarang. It includes 60 lecturers as respondents and the data were collected by using questionnaire and then analyzed by using multiple regression analysis. Results showed that all the hypotheses proposed were accepted in this study. The results of multiple regression analysis indicated positive and significant influence between Islamic work ethic, perceived organizational support, and job satisfaction on organizational citizenship behavior Islamic perspective